(untitled) (Estudos em Design, 2023)
This study addresses people’s resistance to using self-service terminals, especially bank ATMs. Many bank customers prefer seeking assistance from other people or auxiliary professionals when using an ATM. It was observed that this rejection or difficulty of use is not always directly related to bad interface designs of these self-service systems. An in-depth research was conducted, involving observation and a survey on-site at three bank branches in Brazil using the Contextual Inquiry method.The research used the contingency coefficient as a statistical method to determine the magnitude of the correlation between psychological and behavioral factors and ATM aversion.The results verified the existence of Self-service Aversion, which is the tendency of some to prefer human service instead of automated service, and is built upon four main constructs: sense of uncertainty, environment, sense of accountability, and user interface design. It was concluded that user experience is influenced by psychological and behavioral factors, such as expectations, cognition, emotion, motivation, and social context, impacting effectiveness and usability.